2018
DOI: 10.1002/path.5044
|View full text |Cite
|
Sign up to set email alerts
|

Resident cell lineages are preserved in pulmonary vascular remodeling

Abstract: Pulmonary vascular remodeling is the main pathological hallmark of pulmonary hypertension disease. We undertook a comprehensive and multilevel approach to investigate the origin of smooth muscle actin‐expressing cells in remodeled vessels. Transgenic mice that allow for specific, inducible, and permanent labeling of endothelial (Cdh5‐tdTomato), smooth muscle (Acta2‐, Myh11‐tdTomato), pericyte (Cspg4‐tdTomato), and fibroblast (Pdgfra‐tdTomato) lineages were used to delineate the cellular origins of pulmonary va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 39 publications
11
46
0
Order By: Relevance
“…This is further supported by the exclusive expression of the contractile marker DES on ␣SMAϩ cells. This is in line with our previous study where similar results were obtained by using different remodeling stimuli such as hypoxia or allergen challenge (7,19). Additionally, in both our murine models we could show that the percentage of ␣SMAϩ cells expressing DES decreased, while those positive for COL1 increased, suggesting either a shift from a contractile to a synthetic phenotype in ␣SMAϩ cells or expansion of the COL1ϩ/␣SMAϩ population in fibrotic conditions.…”
Section: L693 Fibroblast Diversity In Specific Lung Compartmentssupporting
confidence: 92%
See 2 more Smart Citations
“…This is further supported by the exclusive expression of the contractile marker DES on ␣SMAϩ cells. This is in line with our previous study where similar results were obtained by using different remodeling stimuli such as hypoxia or allergen challenge (7,19). Additionally, in both our murine models we could show that the percentage of ␣SMAϩ cells expressing DES decreased, while those positive for COL1 increased, suggesting either a shift from a contractile to a synthetic phenotype in ␣SMAϩ cells or expansion of the COL1ϩ/␣SMAϩ population in fibrotic conditions.…”
Section: L693 Fibroblast Diversity In Specific Lung Compartmentssupporting
confidence: 92%
“…Expansion of ␣-smooth muscle actin (␣SMA)expressing cells, termed myofibroblasts, is thought to be the major pathomechanism responsible for vascular and parenchymal remodeling. While resident ␣SMAϩ cells are indeed a major pathological cell type that expands and contributes to pulmonary vascular remodeling (7,28), neither vascular nor airway smooth muscle cells represent the major source of interstitial myofibroblasts in lung parenchymal remodeling (10). Furthermore, the simplistic paradigm of myofibroblasts as the single most important cell type in lung fibrosis has been questioned by a recent fate-mapping approach, which showed that ␣SMAϩ cells are not the main source of collagen production (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample preparation and processing were adapted from Crnkovic and colleagues (16). In brief, fresh human lung tissue and isolated PA samples were fixed in 2.5% glutaraldehyde and postfixed in osmium tetroxide.…”
Section: Transmission Emmentioning
confidence: 99%
“…Consistent with previous results, we and others, utilizing BPD animal models, established by hyperoxia exposure, also showed a decrease of endothelial cells in capillaries and blood vessel numbers and an increase of α-Sma positive cells (VSMC) in the tunica media of pulmonary arterioles and normally non-muscularized precapillary arterioles [ 79 , 80 , 81 ]. A lineage tracing study indicated that the expansion of resident SMCs was the major source related to the thickening of the smooth muscle layer in adult PH [ 82 ]. An increased collagen and elastin expression associated with increased α-SMA-positive myofibroblasts, possibly due to endothelial to mesenchymal transition (EndMT), has also been proposed as a mechanism for the accumulation of myofibroblats in the adventitia of pulmonary arteries ( Figure 2 ) [ 83 , 84 ].…”
Section: Development Of Normal Pulmonary Vasculature and Bpd-ph Frmentioning
confidence: 99%